Upaya Mendukung Pencapaian SDGs-13 melalui Edukasi dan Upaya Adaptasi terhadap Kekeringan Pertanian di Desa Batu Rimpang - Saidah, Humairo; Yasa, I Wayan; Budianto, M. Bagus; Salehuddin; Supriyadi, Anid; Hasyim; Karyawan, I Dewa Made Alit; Negara, I Dewa Gede Jaya; Rohani (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Climate change has had a real impact on the agricultural sector, especially in rural areas where the majority of the population depends on agriculture. This community service activity was carried out in Batu Rimpang Village as an academic contribution to enhance community resilience in facing the impacts of climate change through education and the application of water-saving irrigation technology. This program focused on socializing the climate change impacts, followed by hands-on training in installing sprinkler irrigation systems as a simple but effective solution so that farmers can continue to cultivate their land in the limited water availability. The socialization session was carried out interactively and continued with installing sprinkler practice so that participants could understand the technical aspects and benefits of the irrigation system that had been implemented. The training went orderly, attended by around 20 farmers who showed high enthusiasm in each session. This activity has not only increased community’s understanding of climate change adaptation, but also encouraged local initiatives to adopt more efficient and environmentally friendly technologies. It is hoped that this initiative will contribute to the achievement of Sustainable Development Goals (SDGs)-13 on climate action by increasing the adaptive capacity of communities, thereby reducing the potential impacts of climate change in Batu Rimpang village.